Human peritoneal fluid exerts ovulation- and nonovulation-sourced oncogenic activities on transforming fallopian tube epithelial cells - Che-Fang Hsu; Vaishnavi Seenan; Liang-Yuan Wang; Pao-Chu Chen; Dah-Ching Ding; Tang-Yuan Chu (Cancer Cell International)
Abstract Secretory cells in the fallopian tube fimbria epithelium (FTE) are regarded as the main cells of origin of ovarian high-grade serous carcinoma (HGSC). Ovulation is the main cause of FTE oncogenesis, which proceeds through a sequence of TP53 mutations, chromosomal instability due to Rb/cyclin E aberration, in situ carcinoma (STIC), and metastasis to the ovary and peritoneum (metastatic HGSC). Previously, we have identified multiple oncogenic activities of the ovulatory follicular fluid (FF), which exerts the full spectrum of transforming activity on FTE cells at different stages of transformation. After ovulation, the FF is transfused into the peritoneal fluid (PF), in which the FTE constantly bathes. We wondered whether PF exerts the same spectrum of oncogenic activities as done by FF and whether these activities are derived from FF. By using a panel of FTE cell lines with p53 mutation (FT282-V), p53/CCNE1 aberrations (FT282-CCNE1), and p53/Rb aberrations plus spontaneous transformation, and peritoneal metastasis (FEXT2), we analyzed the changes of different transformation phenotypes after treating with FF and PF collected before or after ovulation. Similar to effects exhibited by FF, we found that, to a lesser extent, PF promoted anchorage-independent growth (AIG), migration, anoikis resistance, and peritoneal attachment in transforming FTE cells. The more transformed cells were typically more affected. Among the transforming activities exhibited by PF treatment, AIG, Matrigel invasion, and peritoneal attachment growth were higher with luteal-phase PF treatment than with the proliferative-phase PF treatment, suggesting an ovulation source. In contrast, changes in anoikis resistance and migration activities were similar in response to treatment with PF collected before and after ovulation, suggesting an ovulation-independent source. The overall transforming activity of luteal-phase PF was verified in an i.p. co-injection xenograft mouse model. Co-injection of Luc-FEXT2 cells with either FF or luteal-phase PF supported early peritoneal implantation, whereas co-injection with follicular-phase PF did not. This study, for the first time, demonstrates that PF from ovulating women can promote different oncogenic phenotypes in FTE cells at different stages of malignant transformation. Most of these activities, other than anoikis resistance and cell migration, are sourced from ovulation.